Enhancing Learning Through Athletics in Tanzanian Public Primary Schools: A Case of Kinondoni Municipality - L. Mhina, Evelina; M. Mwila, Prospery (CV Kalimasada Group, 2025)
This study aims to examine the effect of participation in athletic activities on the learning effectiveness of Primary School students in Kinondoni Municipality, Dar es Salaam, Tanzania. This study uses a mixed-method approach with data collection techniques through questionnaires and interviews. A total of 150 participants were involved, consisting of students, teachers, principals, parents, Athletic Club leaders, as well as local education and sports officials. The results of the analysis showed that involvement in athletic activities contributes positively to the improvement of physical fitness, cognitive function, as well as social skills of students, which ultimately increases the effectiveness of learning. However, constraints such as limited resources and cultural barriers are still challenges in the implementation of athletic programs in schools